Evidence-based treatment for children with autism : the CARD model - Granpeesheh, Doreen (Amsterdam : Academic Press, 2014)
This manual is a user-friendly, comprehensive description of the Center for Autism and Related Disorders (CARD) model of autism treatment-the latest scientific information on what truly works in treating autism in an integrated, organized, consumable format. The book details effective early behavioral intervention, covering topics such as challenging behavior, visual modification, parental involvement, improving language, cognition, and social skills, and ends with a section that explains how all of the treatments can be put together in real-life service provision organizations. The CARD mode.
Background. Introduction / Doreen Granpeesheh -- Philosophy and Mores / Doreen Granpeesheh, Jonathan Tarbox -- The diagnosis of autism spectrum disorder / Doreen Granpeesheh, Megan Maixner, Cecilia Knight, Monique Erickson -- Treatment procedures. Principles and procedures of acquisition / Jonathan Tarbox, Doreen Granpeesheh -- A functional approach to challenging behavior / Amy Kenzer -- Visual and other sensory modifications / Carolynn Bredek, Doreen Granpeesheh, Kathy Thompson, Renat Matalon -- Generalization and maintenance / Angela Persicke -- Treatment settings / Mary Ann Cassell -- Parent involvement / Evelyn R. Gould, Vince Redmond -- Program content. Introduction to the center for autism and related disorders curriculum series / Adel C. Najdowski -- Language. Michelle R. Bishop, Adel C. Najdowski -- Play / Jonathan Tarbox, Angela Persicke -- Adaptive / Jonathan Tarbox, Angela Persicke, Ryan Bergstrom -- Motor / Michele R. Bishop -- Academics / Michele R. Bishop, Carolynn Bredek -- Social / Jennifer Yakos -- Cognition / Adel C. Najdowski, Angela Persicke, Evelyn Kung -- Executive functions / Adel C. Najdowski, Angela Persicke, Evelyn Kung -- Treatment oversight. Clinical supervision / Jonathan Tarbox, Adel C. Najdowski -- Data collection and treatment evaluation / Jonathan Tarbox -- Organizational structure / Jonathan Tarbox -- Training and quality control / Cecilia H. Knight -- Ethics / Megan Maixner, Elizabeth Meshes -- Medical treatment and interdisciplinary collaboration / Megan St. Clair, Doreen Granpeesheh -- Standardized assessment / Hilary Adams, Paige Cervantes, Jina Jang, Dennis Dixon -- Looking forward. Technology / Jonathan Tarbox, Adel C. Najdowski -- Research / Jonathan Tarbox -- Global dissemination / Catherine Minch.
Includes bibliographical references and index.
Print version record.
Keywords: Autism in children -- Treatment; Evidence-based medicine; MEDICAL -- Gynecology & Obstetrics; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Autism in children -- Treatment; Evidence-based medicine; Child Development Disorders, Pervasive -- therapy; Evidence-Based Medicine -- methods; Cognitive Behavioral Therapy -- methods; Electronic books; Electronic book